PERKECAMBAHAN BIJI KANTONG SEMAR (Nepenthes gracilis Korth.) SECARA IN VITRO - Isnaini, Yupi; Handini, Elizabeth (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2007)
Mature seeds of a pitcher plant (Nepenthes grocilis Korth.) were cultured in seven different media, namely half strength MS medium, half strength MS medium supplemented with BAP and NAA, 0.8 KC medium supplemented with coconut water + bean sprout extract, 0.8 KC + H3B03 + CuSO3 + ZnSO4 + coconut water + bean sprout extract, 0.25 KC + Vitamin (MS), HYPONeX + coconut water + sprout bean extract, and HYPONeX + potato extract. Each culture was incubated under light conditions. Young seedlings were subsequently transferred onto fresh media of 0.5 MS and 0.25 KC supplemented with 0, 5, 10, and 15 mg/I GA3 after 15 weeks of sowing. Seed germination and seedling growth were observed weekly. It was noted that the seeds started to germinate in ten weeks after incubation and the highest seed germination was obtained in HYPONeX medium + potato extract. However, the appearance of the seedlings was better on MS media and KC media without organic compound than on the other media. Seedlings in all level of GA3 in half strength MS media and 0.25 KC media grew faster than those in media without GA3.